Mechanical properties of ceramics - Wachtman, J. B., 1928- (Wiley, 2009)
Mechanical Properties of Ceramics, Second Edition deals thoroughly with causes of mechanical failure of ceramics (including glass) and design for failure avoidance. Experimental facts and theoretical foundations for mechanical behavior are treated. Probabilistic and mechanistic methods of safe design are described and combined to provide design techniques both for moderate temperatures (brittle behavior) and high temperatures (creep behavior). The competing roles of microstructure in weakening and toughening ceramics are explored and interpreted in terms of reliability improvement through proc.